Pharmacological Responses of the G542X-CFTR to CFTR Modulators - Fang, Xinxiu; Yeh, Jiunn-Tyng; Hwang, Tzyh-Chang (Frontiers in Molecular Biosciences, 2022)
Cystic fibrosis (CF) is a lethal hereditary disease caused by loss-of-function mutations of the chloride channel Cystic Fibrosis Transmembrane conductance Regulator (CFTR). With the development of small-molecule CFTR modulators, including correctors that facilitate protein folding and expression, and potentiators that promote channel activity, about 90% of the CF patients are now receiving efficacious target therapies. G542X-CFTR, a premature termination codon (PTC) mutation, is the most common disease-associated mutation found in the remaining 10% of patients that await effective drugs to rectify the fundamental defects caused by PTC. In this study, we employed biophysical and biochemical techniques to characterize the pharmacological responses of the translational products of G542X-CFTR to a range of new CFTR modulators. Specifically, we identified two different proteins translated from the G542X-CFTR cDNA using Western blotting: the C-terminus truncated protein that responds to the C1 corrector which binds to the N-terminal part of the protein, and a full-length CFTR protein through the read-through process. Electrophysiological data suggest that the read-through protein, but not the C-terminus truncated one, is functional and responds well to CFTR potentiators despite with a lower open probability compared to wild-type CFTR. As the expression of the read-through products can be increased synergistically with the read-through reagent G418 and C1 corrector, but not with combinations of different types of correctors, we concluded that an efficacious read-through reagent is the prerequisite for mitigating the deficits of G542X-CFTR. Moreover, CFTR potentiators may help improve the effectiveness of future combinational therapy for patients carrying PTCs such as G542X.